The Influence of Competence on Employee Performance Through Motivation and Job Satisfaction at Sekolah Luar Biasa Negeri 11 Jakarta - Hilham Maulana; Janiscus Pieter Tanesab (Dinasti Publisher, 2025)
Enhancing employee performance is a vital component in the context of special education, especially within Special Needs Schools (SLB), where human resource management often presents significant challenges. This research investigates the impact of competence on employee performance by incorporating the mediating effects of motivation and job satisfaction, along with the moderating influence of the work environment, with a focus on SLB Negeri 11 Jakarta. A quantitative research design was adopted, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique for data analysis. The findings reveal that competence does not directly affect employee performance; however, it exerts a significant indirect effect through job satisfaction. Motivation did not prove to be a significant mediator, while the work environment was shown to moderate the relationship between competence and performance—albeit negatively. The study provides theoretical contributions to the development of a multidimensional model of performance and offers practical insights for improving human resource strategies in special education settings.